2011
DOI: 10.1371/journal.pone.0017501
|View full text |Cite
|
Sign up to set email alerts
|

Torque Teno Sus Virus (TTSuV) in Cell Cultures and Trypsin

Abstract: Torque teno sus virus (TTSuV), a member of the family Anelloviridae, is a single-stranded, circular DNA virus, widely distributed in swine populations. Presently, two TTSuV genogroups are recognized: Torque teno sus virus 1 (TTSuV1) and Torque teno sus virus 2 (TTSuV2). TTSuV genomes have been found in commercial vaccines for swine, enzyme preparations and other drugs containing components of porcine origin. However, no studies have been made looking for TTSuV in cell cultures. In the present study, a search f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
2

Year Published

2012
2012
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
0
12
2
Order By: Relevance
“…Furthermore, screening of seven additional commonly used cell lines also yielded negative results, as determined by IFA detection (data not shown), indicating that TTSuV contamination in cell cultures is probably not as common as we originally thought. Our result was distinct from that of a recent study by a Brazilian group that reported TTSuV DNA contamination in 15 of 25 cell lines (41). In that study, the five cell lines that were also used in our study, i.e., PK-15, ST, BHK-21, Vero, and MA-104 cells (from which the MARC-145 cell line is derived) were shown to have detectable TTSuV1 and/or TTSuV2 sequences by the use of a one-round duplex PCR assay (41).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Furthermore, screening of seven additional commonly used cell lines also yielded negative results, as determined by IFA detection (data not shown), indicating that TTSuV contamination in cell cultures is probably not as common as we originally thought. Our result was distinct from that of a recent study by a Brazilian group that reported TTSuV DNA contamination in 15 of 25 cell lines (41). In that study, the five cell lines that were also used in our study, i.e., PK-15, ST, BHK-21, Vero, and MA-104 cells (from which the MARC-145 cell line is derived) were shown to have detectable TTSuV1 and/or TTSuV2 sequences by the use of a one-round duplex PCR assay (41).…”
Section: Discussioncontrasting
confidence: 99%
“…Our result was distinct from that of a recent study by a Brazilian group that reported TTSuV DNA contamination in 15 of 25 cell lines (41). In that study, the five cell lines that were also used in our study, i.e., PK-15, ST, BHK-21, Vero, and MA-104 cells (from which the MARC-145 cell line is derived) were shown to have detectable TTSuV1 and/or TTSuV2 sequences by the use of a one-round duplex PCR assay (41). It is unclear why there is such a major discrepancy between the results of our study and those obtained by the Brazilian group.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…For example, porcine trypsin has been traced as the source of Torque teno sus virus (TTSuV), a member of the family Anelloviridae that is a contaminant of many cell lines. Indeed, TTSuV was found in fifteen cell lineages, originating from thirteen different species, and its presence in the cell lines probably traced to the use of porcine trypsin during the propagation of those cells [60]. Anelloviruses are small DNA viruses that replicate within the nuclei of infected cells, and CPE due to their presence have not been well described at present.…”
Section: Adventitious Viruses In Cell-linesmentioning
confidence: 99%
“…However, as typical of these cases, the findings are not published and thus the information not widely disseminated. Reoviruses however can have wide host range and infect many different cell lines [60,64].…”
Section: Adventitious Viruses In Cell-linesmentioning
confidence: 99%